2019
DOI: 10.3389/fpls.2019.00405
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorus Economy of Mediterranean Oak Saplings Under Global Change

Abstract: While a severe decrease in phosphorus (P) availability is already taking place in a large number of ecosystems, drought and nitrogen (N) deposition will likely further decrease the availability of P under global change. Plants have developed physiological strategies to cope with decreasing P resources, but it is unclear how these strategies respond to elevated N deposition and summer droughts. We investigated the influence of N and P availability and soil drought on P uptake (H 3 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have indicated that current climate change leads to an increase in N depositions and an increase in summer droughts causing nutritional imbalances and P deficiencies in ecosystems, making these changes more pronounced in the Mediterranean areas [18][19][20]. For this reason, and although general processes involved in the biochemistry and availability of P are well known, it is necessary to clarify which soil parameters mostly affect each process both in specific ecosystems, mainly in Mediterranean ones, and in different types of soil [21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated that current climate change leads to an increase in N depositions and an increase in summer droughts causing nutritional imbalances and P deficiencies in ecosystems, making these changes more pronounced in the Mediterranean areas [18][19][20]. For this reason, and although general processes involved in the biochemistry and availability of P are well known, it is necessary to clarify which soil parameters mostly affect each process both in specific ecosystems, mainly in Mediterranean ones, and in different types of soil [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of the nutrient uptake efficiencies, drought had an even stronger effect on PUptakeE (as reported in Köhler et al, 2018) than on NUptakeE (cf. Dirks et al, 2019). Drought strongly decreased PUptakeE of beech saplings as a consequence of decreased ECMF colonization rate and the loss of ECMF with longdistance exploration.…”
Section: Soil Drought Disturbs Nutrient Stoichiometry As a Results Of Reductions In Ecmf Diversitymentioning
confidence: 96%